THE INFLUENCE OF FOREIGN DEBT AND FOREIGN INVESTMENT ON INDONESIA’S ECONOMIC GROWTH IN 2011- 2015 - Putri, Delima Oktaviani; Razali, Ramadhan; Malahayatie (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2023)
This article discusses the impact of foreign debt and foreign direct investment (FDI) on Indonesia's economic growth between 2011 and 2015. The paper poses three main questions: (a) what is the impact of foreign debt on Indonesia's economic growth during this period, (b) what is the impact of FDI on the country's economic growth, and (c) what is the impact of both foreign debt and FDI on Indonesia's economic growth simultaneously? The study adopts a quantitative approach and relies on secondary data, specifically time series data obtained from the Indonesian Bureau of Statistics (BPS) and the Ministry of Finance for the period of 2011-2015. The analysis tool used in this research is the Eviews 10 program. The findings of the research indicate that foreign debt (X1) and PMA (X2) did not have a positive and significant impact on Indonesia's economic growth during the period under study. Moreover, the simultaneous impact of foreign debt and PMA on the country's economic growth was also not positive and significant.